2016
DOI: 10.1007/s00404-016-4237-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic supracervical hysterectomy for the larger uterus (>500 g): a case series and literature review

Abstract: The use of LSH for the larger uterus is feasible and safe due to the low level of operative complications as demonstrated in our study and following a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Other authors have since demonstrated that laparoscopic hysterectomy has a very low complication rate (8). The boundaries for both total and supracervical hysterectomy were advanced, supported by good safety data and positive long-term outcomes (9) and increasingly large uteri were removed laparoscopically using modified techniques (10)(11)(12).…”
Section: The Evolution Of Minimal Access Surgery and Morcellationmentioning
confidence: 99%
“…Other authors have since demonstrated that laparoscopic hysterectomy has a very low complication rate (8). The boundaries for both total and supracervical hysterectomy were advanced, supported by good safety data and positive long-term outcomes (9) and increasingly large uteri were removed laparoscopically using modified techniques (10)(11)(12).…”
Section: The Evolution Of Minimal Access Surgery and Morcellationmentioning
confidence: 99%
“…The overwhelming majority of reports demonstrate a minimally invasive approach to be safe and efficient for the removal of large uteri, as shown by acceptably low complication and conversion to laparotomy rates. 24,[28][29][30][32][33][34][35][36][37][38][39][40][41][42][43][44] Even though enlarged uteri were shown to be an independent risk factor for post-hysterectomy morbidity in Louie et al's cohort study, 45 which assessed hysterectomy patient data from more than 500 hospitals (27 167 women in total), abdominal hysterectomy had an overall higher complication rate compared with minimal invasive approaches, even in cases with markedly large uteri. 45 Similar results…”
Section: Discussionmentioning
confidence: 96%
“…Overall, many studies have evaluated the feasibility and safety of laparoscopic hysterectomy for patients with large uteri. The overwhelming majority of reports demonstrate a minimally invasive approach to be safe and efficient for the removal of large uteri, as shown by acceptably low complication and conversion to laparotomy rates 24,28–30,32–44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a new minimally invasive alternative with low preoperative morbidity for total hysterectomy with benign conditions. Furthermore, LASH has benefits such as shorter hospital stays, faster recovery, and faster return to the workplace [8].…”
Section: Laparoscopic Supracervical Hysterectomy (Lsh)mentioning
confidence: 99%